2017
DOI: 10.1590/s0100-204x2017000700005
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for topdressing nitrogen application to common bean using chlorophyll meter

Abstract: -The objective of this work was to establish the diagnostic leaf and the nitrogen sufficiency index (NSI) values most appropriate to estimate N requirement by the 'Pérola' common bean (Phaseolus vulgaris), based on chlorophyll meter monitoring. The diagnostic leaf was defined in an experiment with five N rates, and up to four sampling dates of the diagnostic leaves were evaluated (first, second, and third completely expanded leaves from the apex). Critérios para a aplicação do nitrogênio em cobertura no feijoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…The fact that nitrogen is an extremely mobile element in the plant causes the symptoms of nutritional deficiency to be expressed first in the older leaves (Taiz & Zeiger, 2017); however, the RCI evaluation was performed on the first fully expanded trifoliolate leaf (younger leaves) and may have contributed to the absence of differences. Maia et al (2017) observed the greatest differences in RCI between nitrogen doses when evaluating older leaves (third fully expanded leaf) of common bean compared to younger leaves.…”
Section: Resultsmentioning
confidence: 92%
“…The fact that nitrogen is an extremely mobile element in the plant causes the symptoms of nutritional deficiency to be expressed first in the older leaves (Taiz & Zeiger, 2017); however, the RCI evaluation was performed on the first fully expanded trifoliolate leaf (younger leaves) and may have contributed to the absence of differences. Maia et al (2017) observed the greatest differences in RCI between nitrogen doses when evaluating older leaves (third fully expanded leaf) of common bean compared to younger leaves.…”
Section: Resultsmentioning
confidence: 92%
“…Topdressing N fertilization linearly increased the amount of N accumulated in the shoot of the common bean crop (Figures 2 B and C). , Perez et al (2013), and Maia et al (2017) also found a positive relationship between the amount of N in the common bean shoot and the application of increasing topdressing N rates, which they associated with a greater shoot DM accumulation. In the present study, foliar N application did not interfere with N content and accumulation in the shoot of common bean in the R 8 stage (Table 1).…”
Section: Resultsmentioning
confidence: 79%
“…Nitrogen is the nutrient taken up in the greatest amount by the common bean crop (Perez et al, 2013;Soratto et al, 2013); therefore, its supply at suitable rates and times is fundamental for obtaining a high grain yield (Soratto et al, 2011(Soratto et al, , 2014(Soratto et al, , 2017Amaral et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations